ANALISIS FAKTOR KESULITAN BELAJAR SISWA SEKOLAH DASAR PADA MATERI PECAHAN SERTA SOLUSINYA - Annisa Raudhatul Aulia; Diska Nadia; Masniladevi (Prodi PGMI STAI Sabili Bandung, 2026)
Fraction learning difficulties are a multidimensional and systemic issue in mathematics learning at the primary school level. This study was conducted to comprehensively examine the types of difficulties encountered by students in learning fractions, identify the factors causing these difficulties, and review the solutions recommended in previous studies. The method employed in this study was a literature review of relevant studies published from 2020 to 2026. The findings indicate that the difficulty in learning fractions in elementary school students may be classified into three major categories, namely: (1) challenges in comprehending fundamental fraction concepts, (2) challenges in performing fraction calculations, and (3) difficulties in solving fraction word problems. The factors contributing to these difficulties are sourced from internal and external influences. As a solution, various studies suggest utilizing instructional media and concrete learning approaches, diversifying teaching strategies, enhancing students' learning motivation, and the parental participation in the learning process. This finding hints at the need for a comprehensive and continuous intervention strategy so that the fundamental mathematical understanding understanding of elementary school students can be effectively strengthened